PENINGKATAN KEMAMPUAN MENULIS TEKS FABEL MENGGUNAKAN METODE DISCOVERY LEARNING SMP NEGERI 8 PONTIANAK - Filma, Filma (Universitas Tanjungpura, 2019)
AbstractThis research is motivated by the result of observation which states the lack of writing ability in writing aspect. This is due to several factors one of which is the lack of student interest in writing skills, making it difficult to pour ideas of students. The problem of this study is how the process of learning, activity and motivation of students, and the results of learning discovery learning in students of class VII F SMP Negeri 8 Pontianak?This study was conducted in two cycles. Each cycle consists of planning, acting, observation, and reflecting. The research method used is descriptive method, the research form is qualitative, the research procedure is classroom action research (PTK). Data were taken using test and non test instrument. The data collection tools used are the observation sheet, motivation questionnaire, and the learning result test.The results showed that the discovery learning method can improve the learning result of writing fable text on the students of class VII F SMP Negeri 8 Pontianak. It was found that: (1) learning process of writing fable text using discovery learning method has increased. (2) activity and motivation of student in learning to write text of fable by using discovery learning method each cycle better. (3) learning outcomes are also increasing. This is seen in the average of each cycle, in cycle 1 average 73.96, cycle 2 increased to 85.68. (4) students' attitudes following learning improved greatly.Â Keywords: Writing skill, Text Fable, Discovery Learning Method.